2023
DOI: 10.22146/ijc.73234
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Al and Cu Doping on the Structure, Morphology, and Optical Properties of ZnO Thin Film

Abstract: In this study, ZnO thin films doped with Al (AZO) and Cu (CZO) were fabricated on a glass substrate via sol-gel spin coating. The influence of 1 atomic % Al and Cu doping on the structure, morphology, as well as optical properties of ZnO thin film was then analyzed with X-ray diffraction (XRD), atomic force microscopy (AFM), and UV-Vis spectroscopy. XRD analysis revealed that all samples possessed hexagonal wurtzite crystal structures with 3 to 4 preferred orientations. Al and Cu doping caused a decrease in cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Previous research also showed that the width of Eg is influenced by crystallite size, morphology, and synthesis method of nano-ZnO [49,55]. The observed bandgap energies showed that nano-ZnO-1 and nano-ZnO-2 were suitable as photocatalytic materials primarily for absorption of UV light [56][57][58].…”
Section: Characterization Optical Spectramentioning
confidence: 87%
“…Previous research also showed that the width of Eg is influenced by crystallite size, morphology, and synthesis method of nano-ZnO [49,55]. The observed bandgap energies showed that nano-ZnO-1 and nano-ZnO-2 were suitable as photocatalytic materials primarily for absorption of UV light [56][57][58].…”
Section: Characterization Optical Spectramentioning
confidence: 87%